2009
DOI: 10.1890/08-1742.1
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient availability and phytoplankton nutrient limitation across a gradient of atmospheric nitrogen deposition

Abstract: Atmospheric nitrogen (N) deposition to lakes and watersheds has been increasing steadily due to various anthropogenic activities. Because such anthropogenic N is widely distributed, even lakes relatively removed from direct human disturbance are potentially impacted. However, the effects of increased atmospheric N deposition on lakes are not well documented. We examined phytoplankton biomass, the absolute and relative abundance of limiting nutrients (N and phosphorus [P]), and phytoplankton nutrient limitation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
113
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(119 citation statements)
references
References 44 publications
4
113
1
1
Order By: Relevance
“…However, P limitation alone was not reported at the highest N deposition site (AT7). A shift from N to P limitation has previously been reported at rates[6 kg ha -1 year -1 (Bergström et al 2005;Elser et al 2009b), far in excess of atmospheric N deposition currently estimated for Greenland (\1 kg N ha…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…However, P limitation alone was not reported at the highest N deposition site (AT7). A shift from N to P limitation has previously been reported at rates[6 kg ha -1 year -1 (Bergström et al 2005;Elser et al 2009b), far in excess of atmospheric N deposition currently estimated for Greenland (\1 kg N ha…”
Section: Discussionmentioning
confidence: 92%
“…P) exerts the greatest control over phototrophic growth and how this might change in response to variation in nutrient supply (e.g. Levine and Whalen 2001;Bergström et al 2005;Elser et al 2009aElser et al , 2009bSymons et al 2012). A common feature of many of these studies is a focus on nutrient limitation of phytoplankton growing in the open water column (Levine and Whalen 2001;Jansson 2006, 2008;Elser et al 2009a, b).…”
Section: Introductionmentioning
confidence: 99%
“…Burns 2003). This increase of DIN in wetfall at high elevation in the Colorado Rocky Mountains has resulted in this area becoming N-saturated (Williams et al 1996a), leading to higher concentrations of nitrate in surface waters (Baron et al 1994;Williams and Tonnessen 2000), and shifted phytoplankton nutrient limitation from predominant nitrogen (N) and joint N and phosphorus (P) limitation to predominant P limitation (Elser et al 2009). An outstanding question remains: is increased nitrate in surface waters of highelevation catchments in the Colorado Rockies from nitrate in wetfall directly transported to surface waters, or is it a result of net nitrification induced by DIN in wetfall?…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has shown that phytoplankton production is naturally Nlimited in lakes subject to low rates of N deposition (Bergströ m et al 2008, Elser et al 2009a. Furthermore, enhanced anthropogenic N deposition has resulted in elevated TN:TP ratios in many lakes in the northern hemisphere, and a corresponding shift from N-to P-limitation (Bergströ m et al 2005, Elser et al 2009a), which in turn has increased phytoplankton biomass (Bergströ m and Jansson 2006) and elevated sestonic N:P ratios (Elser et al 2009b). It has also been shown that phytoplankton P-limitation induced by high N deposition impairs the growth of consumers with high P demand due to food quality constraints and low P content in phytoplankton (Elser et al 2010).…”
Section: Introductionmentioning
confidence: 99%